Baseband Transceiver Design of a High Definition Radio FM System Using Joint Theoretical Analysis and FPGA Implementation. (16th April 2014) - Chen, Chien-Sheng; Lu, Chyuan-Der; Shou, Ho-Nien; Lin, Le-Wei
Abstract : Advances in wireless communications have enabled various technologies for wireless digital communication. In the field of digital radio broadcasting, several specifications have been proposed, such as Eureka-147 and digital radio mondiale (DRM). These systems require a new spectrum assignment, which incurs heavy cost due to the depletion of the available spectrum. Therefore, the in-band on-channel (IBOC) system has been developed to work in the same band with the conventional analog radio and to provide digital broadcasting services. This paper discusses the function and algorithm of the high definition (HD) radio frequency modulation (FM) digital radio broadcasting system. Content includes data format allocation, constellation mapping, orthogonal frequency division multiplexing (OFDM) modulation of the transmitter, timing synchronization, OFDM demodulation, integer and fraction carrier frequency (integer carrier frequency offset (ICFO) and fractional CFO (FCFO)) estimation, and channel estimation of the receiver. When we implement this system to the field programmable gate array (FPGA) based on a hardware platform, both theoretical and practical aspects have been considered to accommodate the available hardware resources.